The Influence of Visualization of Food Appearance and Food Quality Towards Customer Satisfaction in Tutup Panci Bistro, Bumi Serpong Damai, South Tangerang - Putra, Aditya Nova; Wulan, Saptarining; Ingkadijaya, Rahmat (Institut Pariwisata Trisakti, 2018)
Nowadays, Visualization of food appearance has become an important factor in influencing customer satisfaction which is creating an unforgettable experience when people visit to the restaurant. The aspect of visualizing the appearance of food must also be balanced by good food quality in the restaurant. The purpose of this study was to identify the effect of visualization of food appearance and food quality in achieving customer satisfaction in Tutup Panci Bistro. In this study, visualization of food appearance has five important factors that support in achieving customer satisfaction, which are; component of the material used, color selection, food texture, shape and size, and layout. Therefore, in previous study, quality of food has three important factors, which are: the taste of food, the variety of menus, and the nutritional content of food. The methodology used in this study was quantitative and qualitative, whereas, quantitative data collection was obtained through questionnaires to 100 guests at Tutup Panci Bistro. Meanwhile, qualitative data is obtained through interviews with food influencers / reviewers. Based on the results obtained, appearance and quality of food have a significant positivity influence towards customer satisfaction at Tutup Panci Bistro.